A review of the management of complex para-pneumonic effusion in adults - Koppurapu, Vikas; Meena, Nikhil (Journal of Thoracic Disease, 2017)
A complex para-pneumonic effusion is a descriptive term for exudative effusions, which complicate or are likely to complicate the anatomy of the pleural space after pneumonia. We performed an online search was performed using the resources PubMed and Google Scholar to provide an update on the management of such effusions based on review of published literature. Search terms including pleural effusion (PE), parapneumonic effusion, and empyema were used. Relevant studies were identified and original articles were studied, compared and summarized. References in these articles were examined for relevance and included where appropriate. Studies involving pediatric patients were excluded. Management of para-pneumonic PE has changed tremendously over the last decade. As we accumulate more evidence in this area, approach to pleural fluid drainage is becoming more specific and guideline based. An example of a practice changing study in this aspect is the Multi-center Intrapleural Streptokinase Trial (MIST) 2 trial which demonstrated that a combination of intra-pleural tPA and DNAse improved outcomes in pleural infections compared to DNase or t-PA alone. More randomized control trials are needed to describe the role of surgical techniques like VATS (video-assisted thoracoscopic surgery) when MIST 2 protocol fails; this combination has revolutionized the management of empyema in recently.